Power And Ideology In Barks' Translations Of Rumi's Poetry - Abbaspour, Bita Naghmen (2017)
Translation of ideology and its relation to power is one of the main concerns of the contemporary studies of the discipline of translation studies. Accordingly the current study explored translator’s ideological manipulative strategies, which were imposed on to the text backdrop by the target socio-cultural context. The study employed CDA as its theoretical and analytical tool. As in ideological explorations of translation, analyzing merely the text cannot provide a comprehensive perspective; thus, the present study chose both text and context as its discourse.